Improving English Vocabulary By Using Picture Media For Class VII Students of MTs NW Karang Juli - St. Hartini; Wahyudin; Moh. Zalhairi (STKIP Al-Amin Dompu, 2024)
This study aims to determine the use of images in improving students' vocabulary mastery and to investigate students' perceptions of the use of images. This study was conducted at MTs NW Karang Juli Kadindi. The subjects of this study were 29 students of MTs NW Karang Juli. This study was conducted using Classroom Action Research by Kemmis and Mc Taggart which consisted of 2 cycles. The data of this study are qualitative data. Qualitative data were obtained from students' main scores in the test; pre-test, post-test I and post-test II. While qualitative data were obtained from observation sheets, interviews and documentation that had been compiled by researchers during the teaching and learning process. The results of the data analysis showed that there was an increase in students' vocabulary mastery from each cycle. This is indicated by the average pre-test score of 54.31. Where, there were 7 students who obtained a successful criterion score or only 24.13% and 24 students were unsuccessful or 75.86%%. After conducting cycle I using images, there was an increase in students' average results of 67.27%. Where, 19 students obtained a successful criterion score or only 65.51% and 10 students obtained a failed criterion score or 34.48%. Then making improvements for the second cycle after reflection on the first cycle, there was an average increase in students of 76.03%. Where, 24 students obtained a successful criterion score or 86.20% and 4 students obtained a failed criterion score or 13.79%.